Striatal Distribution and Cytoarchitecture of Dopamine Receptor Subtype 1 and 2: Evidence from Double-Labeling Transgenic Mice - Ren, Keke; Guo, Baolin; Dai, Chunqiu; Yao, Han; Sun, Tangna; Liu, Xia; Bai, Zhantao; Wang, Wenting; Wu, Shengxi (Frontiers in Neural Circuits, 2017)
As the main input nucleus of the basal ganglion, the striatum executes different functions, including motivation, reward, and attention. The functions of the striatum highly rely on its subregions that receive projections from various cortical areas and the distribution of striatonigral neurons that express D1 dopamine receptors (or D1 medium-sized spiny neurons, D1 MSNs) and striatopallidal neurons that express D2 dopamine receptors (or D2 MSNs). Using BAC transgenic mice, several studies have recently been performed on the spatial distribution of D1 and D2 MSNs. However, these studies mainly focused on enumeration of either Drd1a-enhanced fluorescent protein (eGFP) or Drd2-eGFP in mice. In the present work, we used Drd1a-tdTamato and Drd2-eGFP double BAC transgenic mice to evaluate the spatial pattern of D1 MSNs (red fluorescence) and D2 MSNs (green fluorescence) along the rostro-caudal axis of the dorsal striatum. The dorsal striatum was divided into three subregions: rostral caudoputamen (CPr), intermediate CP (CPi), and caudal CP (CPc) across the rostral–caudal extent of the striatum. The results demonstrate that D1 and D2 MSNs were intermingled with each other in most of these regions. The cell density of D1 MSNs was slightly higher than D2 MSNs through CPr, CPi, and CPc, though it did not reach significance. However, in CPi, the ratio of D1/D2 in the ventromedial CPi group was significantly higher than those in dorsolateral, dorsomedial, and ventrolateral CPi. There was similar proportion of cells that co-expressed D1 and D2 receptors. Moreover, we demonstrated a pathway-specific activation pattern of D1 MSNs and D2 MSNs in a manic like mouse model induced by D-Amphetamine by utilizing this double transgenic mice and c-fos immunoreactivity. Our results may provide a morphological basis for the function or pathophysiology of striatonigral and striatopallidal neurons with diverse cortical inputs to the dorsal striatum.